2021
DOI: 10.3389/fphar.2021.738316
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Adaptive Immune Cell and NK Cell Subsets in Patients With Ankylosing Spondylitis After IL-17A Inhibition by Secukinumab

Abstract: Background: Anti-IL-17A therapy is generally effectively applied in patients with Ankylosing Spondylitis (AS) to achieve and maintain remission. However, the influence of anti-IL-17A on the composition of the immune system is not apparent. Our prospective study was to explore the changes in immune imbalance regarding T cell, B cell and natural killer (NK) cell subsets after secukinumab treatment in AS patients.Methods: Immune cell distribution of 43 AS patients treated with secukinumab for 12 weeks and 47 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
(34 reference statements)
1
2
1
Order By: Relevance
“…Following the study hypothesis, combined therapy slightly decreased circulating Th1 cells and stabilized Treg cells during the follow-up. In contrast with our findings, Treg cells decreased in skin lesions from patients with psoriasis treated with SCK 41 and decreased peripheral Treg cells in ankylosing spondylitis patients 42 . During IL-17A blockade, peripheral Treg cells remained stable, potentially enhancing the safety of IL-17 inhibition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Following the study hypothesis, combined therapy slightly decreased circulating Th1 cells and stabilized Treg cells during the follow-up. In contrast with our findings, Treg cells decreased in skin lesions from patients with psoriasis treated with SCK 41 and decreased peripheral Treg cells in ankylosing spondylitis patients 42 . During IL-17A blockade, peripheral Treg cells remained stable, potentially enhancing the safety of IL-17 inhibition.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, the solitary use of SCK did not show benefit in proteinuria, as per the study and some clinical cases 22 24 , 27 . While Treg cell counts were stabilized in our study, a decrease in Treg cell numbers has been observed in cutaneous tissue and at peripheral levels in ankylosing spondylitis 42 . In light of our hypothesis, this could be potentially detrimental if IL-17 is blocked.…”
Section: Discussionsupporting
confidence: 41%
“…Previous research has suggested that symptom clusters in cancer may share some mutual biological mechanisms, including pro‐inflammatory cytokines 19 . As an inflammatory disease, AS has elevated levels of pro‐inflammatory cytokines, altered immune cell distribution 20 and also concurs with pain, fatigue, sleep disturbance, and depression 8 . The possible mechanisms of the 4 symptom clusters were discussed based on the literature.…”
Section: Discussionmentioning
confidence: 99%
“…TNF inhibitors (TNFi) showed good response rates in CD8+NK cell subsets [ 89 ]. However, treatment with secukinumab showed no change in NK cells in patients with AS [ 90 ]. An altered NK cell population could be a cell-based parameter for the selection of therapeutic agents.…”
Section: Progression Of Inflammationmentioning
confidence: 99%